Dietary supplementation with a novel acidifier sodium diformate improves growth performance by increasing growth-related hormones levels and prevents Salmonella enterica serovar Pullorum infection in chickens - Sun, Yufan; Zhang, Xiaofen; Han, Weiyao; Liao, Weilian; Huang, Jing; Chen, Yong; Li, Hengzhang; Chen, Xiabing; Huang, Qi; Zhou, Rui; Li, Lu (Frontiers in Veterinary Science, 2024)
Since the use of antibiotics as growth promoters in animal feed has been restricted or banned in several countries, finding suitable alternatives is crucial for maintaining animal health. In this study, a novel formate acidifier named sodium diformate (NaDF) was synthesized. and the effects on growth performance and the prevention effects against Salmonella enterica serovar Pullorum infections in chickens were assessed. In broilers, NaDF supplementation improved growth performance, as evidenced by increased body weights and reduced feed conversion ratios. At 38 days of age, NaDF supplementation increased the levels of growth-hormone and ghrelin in the serum, lowered pH values in the gut, improved duodenal morphology, as shown by increased villus length/crypt depth ratios. NaDF also modulated the abundance of beneficial and harmful bacteria without changing the general microbiota diversity and short-chain fatty acids levels, which would be beneficial for maintaining gut homeostasis during its use. NaDF exhibited a broad spectrum of antibacterial activity in vitro. Supplementation with NaDF effectively decreased S. Pullorum colonization in the cecum, liver and spleen in chickens, and mitigated pathological changes in the tissues. Therefore, as a novel acidifier, NaDF can improve chicken growth performance by increasing growth-related hormones levels while maintaining the diversity of gut microbiota, and also resist intestinal bacterial infection. These results provided evidences for the application of NaDF as an effective and safe animal feed in poultry farming.